RECOVERY OF OVERRIPE BANANAS FOR BIOETHANOL PRODUCTION - MARIA CRISTIANA GARNAI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2014)
This paper aimed the capitalization of overripe bananas that can no longer be used as fruits for consumption. Bananas fermentation was performed in several variants depending on the fermentation agent (yeasts) and on the different nutrients and growth promoters added to the fermentation media. The research aimed to establish an optimal bioconversion of the banana carbohydrates into ethanol.